2020
DOI: 10.1016/j.imbio.2020.151950
|View full text |Cite
|
Sign up to set email alerts
|

GTS-21, an α7nAChR agonist, suppressed the production of key inflammatory mediators by PBMCs that are elevated in COPD patients and associated with impaired lung function

Abstract: Chronic obstructive pulmonary disease (COPD) is a lung inflammatory disease characterized by progressive airflow limitation, chronic respiratory symptoms and frequent exacerbations. There is an unmet need to identify novel therapeutic alternatives beside bronchodilators that prevent disease progression. Levels of both Nitric Oxide (NO) and IL-6 were significantly increased in the plasma of patients in the exacerbation phase (ECOPD, n = 13) when compared to patients in the stable phase (SCOPD, n = 38). Levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 62 publications
0
17
0
2
Order By: Relevance
“…Altogether, understanding the repartition and the possible assembly of nAChRs at the cancer cell surface may pave the way towards the design of effective anti-cancer drugs. (ii) nAChR SNPs were also associated with nicotine dependence and COPD [ 50 , 51 , 52 , 53 , 54 ]. CHRNA3/A5/B4 polymorphisms were heavily discussed in the dissection of the genetic origins of COPD, but no functional studies have been published so far [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, understanding the repartition and the possible assembly of nAChRs at the cancer cell surface may pave the way towards the design of effective anti-cancer drugs. (ii) nAChR SNPs were also associated with nicotine dependence and COPD [ 50 , 51 , 52 , 53 , 54 ]. CHRNA3/A5/B4 polymorphisms were heavily discussed in the dissection of the genetic origins of COPD, but no functional studies have been published so far [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…CHRNA3/A5/B4 polymorphisms were heavily discussed in the dissection of the genetic origins of COPD, but no functional studies have been published so far [ 55 ]. In addition, α7 and its ligands received particular attention as potential inflammatory players in COPD patients [ 54 , 56 ]. Exploring the involvement of nAChRs in COPD pathogenesis and progression in light of their differential distribution in lung cell populations may help improve health care for this pathology lacking treatments.…”
Section: Discussionmentioning
confidence: 99%
“…(i) nAChRs single nucleotide polymorphisms (SNP) were associated to lung cancer cells [36,37] and nAChRs were shown to be involved in cancer cell proliferation and survival [38][39][40][41]. (ii) nAChRs SNPs were also associated with nicotine dependence and COPD [42][43][44][45][46]. (iii) Nicotine, the main ligand of nAChRs, and more generally smoking, have been shown in vitro and in vivo to modulate the expression of hACE2, the main receptor of SARS-CoV-2 spike S protein [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, procalcitonin, C-reactive protein (CRP) and IL-6 levels diminished with physostigmine treatment (17). Recent study revealed that GTS-21 improved lung function along with the reduction in plasma IL-6 level in patients with chronic obstructive pulmonary disease (46). Additionally, α7nAChR positive allosteric modulator and well-known antiparasitic drug ivermectin has been shown to reduce viral replication effectively in-vitro.…”
Section: Clinical Evidence Of Beneficial Effects Of Cholinergic Agonimentioning
confidence: 99%